POLITICAL MARKETING MANAGEMENT: DISCOURSE ON THE EMERGING TREND IN POLITICAL ANALYSIS - Onebamhoi Obakhedo, Neville; Eshi Obakhedo, Monica (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
At the heart of politicking between political actors and political decision-makers in the electoral and political processes resulting in electoral outcomes, actions and policies of government is the concept of political marketing. Political marketing resonates in local and international politics when ideas, ideologies and philosophies among others are exported from one part of the nation-state to the other or from one part of the world to another. It is trite to note that the development of the concept of political marketing and political marketing management is not a new phenomenon. What is novel that arouses intellectual curiosity is the deployment of political marketing management as a tool for political analysis either on the local or international scene. To this end, the objective of this paper is to enhance a deeper and better understanding of the concept with a view to lay bare its significance and marketing management utility in political analysis in relation to political tactics, strategies and tools. The objective also includes showing the relationship between politics and marketing and how this relationship reinforces political marketing management as a tool for political analysis. The methodology used for gathering and analyzing information concerning this paper was the secondary data gathering method. This was carried out by examining existing literature, following and tracking inter-party politics as they relate to issues of campaigns and electioneering, governance, service delivery and news reportage from the media on the political process. As part of the findings, it is discovered that there is significant relationship between politics and marketing and this has helped political actors and decision-makers in their reactions, maneuvers and change of tactics to happenings in the political market place. Also, findings show political marketing management has become an emerging trend for political analysis in this contemporary era of information revolution and democratic resurgence. The paper concludes by recommending a wider scope of political marketing management to include good governance and effective service delivery so that those who market politics should not rely only on campaigns and propaganda machineries while attempting to trade politics.